An Unusual Case of Systemic Inflammatory Myofibroblastic Tumor with Successful Treatment with ALK-Inhibitor - Sanjivini V. Jacob; John D. Reith; Angerika Y. Kojima; William D. Williams; Chen Liu; Lizette Vila Duckworth (Hindawi Limited, 2014)
Systemic inflammatory myofibroblastic tumor is an exceedingly rare entity. A 45-year-old Hispanic female presented with a 6-month history of left-sided thigh pain, low back pain, and generalized weakness. PET/CT scan revealed abnormal activity in the liver, adrenal gland, and pancreas. MRI of the abdomen demonstrated two 6-7 cm masses in the liver. MRI of the lumbar spine demonstrated lesions in the L2 to L4 spinous processes, paraspinal muscles, and subcutaneous tissues, as well as an 8 mm enhancing intradural lesion at T11, all thought to be metastatic disease. A biopsy of the liver showed portal tract expansion by a spindle cell proliferation rich in inflammation. Tumor cells showed immunoreactivity for smooth muscle actin and anaplastic lymphoma kinase 1 (ALK1). Tissue from the L5 vertebra showed a process histologically identical to that seen in the liver. FISH analysis of these lesions demonstrated an ALK (2p23) gene rearrangement. The patient was successfully treated with an ALK-inhibitor, Crizotinib, and is now in complete remission. We present the first reported case, to our knowledge, of inflammatory myofibroblastic tumor with systemic manifestations and ALK translocation. This case is a prime example of how personalized medicine has vastly improved patient care through the use of molecular-targeted therapy.